SCAI expert consensus statement update on best practices for transradial angiography and intervention. Issue 2 (27th December 2019) - Shroff, Adhir R.; Gulati, Rajiv; Drachman, Douglas E.; Feldman, Dmitriy N.; Gilchrist, Ian C.; Kaul, Prashant; Lata, Kusum; Pancholy, Samir B.; Panetta, Carmelo J.; Seto, Arnold H.; Speiser, Bernadette; Steinberg, Daniel H.; et al.
Abstract: Transradial angiography and intervention continues to become increasingly common as an access site for coronary procedures. Since the first "Best Practices" paper in 2013, ongoing trials have shed further light onto the safest and most efficient methods to perform these procedures. Specifically, this document comments on the use of ultrasound to facilitate radial access, the role of ulnar artery access, the utility of non‐invasive testing of collateral flow, strategies to prevent radial artery occlusion, radial access for primary PCI and topics that require further study.